Genome-wide analyses of non-syndromic cleft lip with palate identify 14 novel loci and genetic heterogeneity - Yanqin Yu (Nature Communications, 2017)
Non-syndromic cleft lip with palate is a common birth defect of unknown aetiology. Here, the authors discover 14 new genes associated with this condition, and show genetic heterogeneity in this and other non-syndromic orofacial clefting disorders.